The Mad Border Body: A Political In-betweeness - Kafai, Shayda (Disability Studies Quarterly, 2012)
Sanity and madness have historically and culturally functioned as binary opposites, the former serving as a representation of normalcy, while the latter functions as shorthand for defect and abnormality. This essay examines the artificiality of this binary construction and offers the mad border body as an alternative. Informed by the works of Chicana theorist Gloria Anzaldúa and queer theorist Jacquelyn N. Zita, the mad border body argues that one can simultaneously inhabit the spaces of sanity and madness. As a third positionality, the mad border body is an alternative to the sane/mad construction in that it advocates for a disruption of binary logic all together. In its examination of this alternative location of being, this essay is also grounded in the author’s own bodily experiences with madness, in her own phenomenology of disability. Keywords: madness, sanity, phenomenology of disability, mad border body